Establishment Of Tissue Culture Planting Materials Of Ficus Carica L. Red Libyan Cultivar - Kho, Ying Han (2024)
Ficus carica L. cv. Red Libyan, a member of the Moraceae family, is a cultivar of the common fig tree known for its purplish red fruit. This variety is known for its sweet and flavoursome figs, making it popular with fig lovers and gardeners. The micropropagation of Ficus carica L. cv. Red Libyan has been successfully established through a series of systematic experiments and studies. The cultivation and propagation of Ficus carica L. cv. Red Libyan can be challenging using traditional methods. This is due to factors such as slow growth, susceptibility to diseases and limited availability of planting material. In addition, a lack of optimised tissue culture protocols specifically for this variety hinders its efficient mass multiplication and genetic improvement. Therefore, the aim of this study was to develop an efficient and reproducible micropropagation protocol for this fig cultivar as well as to evaluate its morphological and genetic stability. The study included sterilisation of apical bud surfaces, regeneration of mature plantlets and in vitro propagation with different growth regulators and culture conditions. In particular, the combination of 20 μM TDZ + 1 μM NAA + 1.0 g L-1 activated charcoal medium showed the most favourable growth parameters, including shoot length, leaf number, root number and root length. Red:blue LED light was found to promote higher shoots during plantlet development. An acclimatisation protocol was successfully carried out and resulted in a 100 % survival rate of the plantlets.